The Effect of Hedonic Motivation and Consumer Attitudes Towards Purchase Decision on K-Pop CD Albums (Study on KPOPSURABAYA Community) - Devita Anggraini Lestari; Monika Tiarawati (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2020)
The rapid enthusiasm of Korean pop music or K-Pop is very high among the millennial generation. The mushrooming of online music streaming like Joox, Spotify, Apple music has made the CD album sales threatened. However, K-Pop fans apparently are still enthusiastic about buying a CD album even though the price is quite expensive. This study discusses the hedomic motivations and consumers attitudes towards purchasing decisions. This type of research used in this study is a combination of purposive sampling techniques. Data collection is done by using an online questionnaire using Google forms. The statistical analysis used in this study uses SPSS and data analysis techniques in this study use the classic assumption test, multiple linear regression analysis, and hypothesis testing. It can be explained that the results of the analysis show that hedonic motivations and consumer attitudes has significant influential on purchasing decisions.